Computation of Vertex-Based Topological Indices of Middle Graph of Alkane CtH2t+2. (30th May 2022) - Sardar, Muhammad Shoaib; Siddique, Imran; Jarad, Fahd; Ali, Muhammad Asad; Türkan, Erkan Murat; Danish, Muhammad
Abstract : Alkanes are the primary constituents of methane or natural gas that can also be found in volcanic crust. As a result of methane as a heat source, humans may cook without using any fuel in a volcanic environment. Propane which is an alkane derivative is safer alternative to methane and is commonly present in gas cooking fuel, as well as a tiny amount of gasoline and matches. The primary ingredient in automobile especially gasoline is also alkane in the form of octane. Topological indices are largely applied in chemistry to improve the quantitative structure relationship in which the properties of the molecules can be linked with their chemical structures. In this research work, we will calculate the certain well-known topological indices of the middle graph of alkane based on vertex degree and also present a numerical and graphical comparison of computed topological indices.